PENGARUH INVERTER SEBAGAI ALAT PENGENDALI FREKUENSI TERHADAP UNJUK KERJA MOTOR INDUKSI TIGA FASE SANGKAR TUPAI - , DARU KUMOLO; , Ir. Bambang Sugiyantoro, M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Electric Machines have significant role to support daily activities, both in industry and households. One of the commonly used electric machines is an induction motor. It has advantages over other types of motors, which are high efficiency, simple and robust construction, and easy in maintenance. One of the weaknesses of the induction motor is difficult to control the speed. With an inverter, the speed of an induction motor can be controlled by changing the input frequency . In this research, the influence of the inverter to the induction motorâs performance when controling the speed of induction motor is investigated. This research is performed by comparing an induction motor working without inverter and one with inverter under load conditions. When using inverter, the frequency was changed from zero to 60 Hz with 10 Hz increment to know the influence on performance of induction motor. Parameters to be observed is the voltage, current, active power, reactive power, power factor, rotor speed, slip, and efficiency. Based on the test results, it can be concluded that when motor working with inverter, frequency is linear to the current, active power, reactive power, power factor, rotor speed, efficiency, but it is inversely related to the slip. When the motor working without inverter as compared to when the motor working with inverter at 50 Hz, the inverter will cause a current, active power, reactive power becomes larger, while the efficiency and power factor will decrease.